2022
DOI: 10.1002/ps.6844
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of thermotolerant Beauveria bassiana isolates and with insecticidal activity against the cotton‐melon aphid Aphis gossypii (Glover) (Hemiptera: Aphididae)

Abstract: BACKGROUND: Cotton-melon aphid Aphis gossypii (Glover) causes severe damage mainly to cucurbits. Twenty-two Beauveria sp. isolates were simultaneously assessed for their pathogenicity and heat tolerance. The selected isolates were identified molecularly and characterized in terms of conidial germination rate, mycelial growth, conidial yield and endophytic activity. RESULTS: Screening bioassays showed that the B. bassiana isolates B3, B7, B9 and B12 were the most toxic, inducing mortality equal to or slightly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 143 publications
(313 reference statements)
0
8
0
Order By: Relevance
“…53 Mseddi et al screened a wild strain of B. bassiana B12 that not only promoted several plant growth parameters at 5 weeks after root inoculation, but also displayed higher toxicity toward the cotton-melon aphid Aphis gossypii (Glover) than the commercialized B. bassiana BNat strain following colonization in cotton plants. 54 Some research suggests that EPF have the capacity to transfer nutrients to plants, 55,56 and the growth and virulence of EPF increased depending on the colonization of plants. 40 Thus, it is necessary to find new EPF strains that can confer plant resistance against biotic stress through endogenous colonization.…”
Section: Discussionmentioning
confidence: 99%
“…53 Mseddi et al screened a wild strain of B. bassiana B12 that not only promoted several plant growth parameters at 5 weeks after root inoculation, but also displayed higher toxicity toward the cotton-melon aphid Aphis gossypii (Glover) than the commercialized B. bassiana BNat strain following colonization in cotton plants. 54 Some research suggests that EPF have the capacity to transfer nutrients to plants, 55,56 and the growth and virulence of EPF increased depending on the colonization of plants. 40 Thus, it is necessary to find new EPF strains that can confer plant resistance against biotic stress through endogenous colonization.…”
Section: Discussionmentioning
confidence: 99%
“…For example, endophytic colonization by B. bassiana and M. anisopliae in maize plants affects the fitness of S. frugiperda , and both strains negatively impact the development and fecundity of S. frugiperda ( Altaf et al, 2023 ). Sinno et al (2021) found that aphids reared on B. bassiana -treated plants for their entire lifespan were negatively affected in terms of survival and fertility in comparison with control cohorts; Mseddi et al (2022) screened a wild strain of B. bassiana B12 that not only promoted several plant growth parameters after root inoculation, but also displayed toxicity toward A. gossypii following colonization in cotton plants. Zhu et al (2023) found that B. bassiana -inoculated maize plants can influence the eggs laying selectivity of O. furnacalis females by changing plant volatile profiles; and González-Mas et al (2021) found that when the cotton was colonized by B. bassiana , they emit a different blend of volatile compounds compared to uncolonized control plants, which can affect the feeding behavior of insect pests A. gossypii , S. frugiperda , and S. littoralis .…”
Section: Discussionmentioning
confidence: 99%
“…In the past, acquisition of high-virulence strains of B. bassiana has mainly involved isolation and screening of wild strains collected from the eld using biological testing, which is time-consuming and labour-intensive [74,75]. Here, we found that mycoviruses may be a key factor causing the decline of B. bassiana virulence, and virus detection could be used to exclude hypovirulent virus-infected strains, and to screen strains of wild B. bassiana with high virulence, thereby improving the e ciency of high virulence strain screening.…”
Section: Discussionmentioning
confidence: 99%